MEDICATION ADHERENCE IN CARDIOVASCULAR HEALTH: UNDERSTANDING PATIENTS AND HEALTHCARE PROFESSIONALS’ PERSPECTIVES, CHALLENGES, AND SUSTAINABLE STRATEGIES - Adnan Yaqoob; Rubina Barolia; Laila Akbar Ladak; Furqan Yaqub Pannu; Aamir Hameed Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Medication non-adherence poses substantial risks, including disease progression, increased hospitalizations, and elevated healthcare costs. Understanding the importance of medication adherence and the unique challenges faced by individuals with CVD in Pakistan is essential for implementing targeted interventions and improving patient outcomes. This research aims to explore the understanding and challenges of medicine adherence in patients with coronary artery disease and healthcare professionals' perspectives on practical strategies for Pakistani patients.Methods: Data were collected from 30 participants through in-depth, semi-structured interviews. The sample comprised 20 patients who had suffered a heart attack at least six months ago and 10 healthcare professionals, including cardiologists, nurses, and pharmacists. Data were analyzed using NVIVO software with a thematic analysis approach.Results: There were total of eight themes emerged from the qualitative data shared by the participants: Patient Understanding and Acceptance of Medication for Cardiovascular Health, Financial, and Practical Challenges in Medication Adherence, Strategies for Sustainable Medication Adherence, Patient-Centered Medication Education and Engagement, Patient Motivation and Understanding in Medication Adherence, Empowering Patients in Long-Term Medication Management, Inconsistency in Patient Education Across Healthcare Providers, and Healthcare Accessibility and AffordabilityConclusion: The data from qualitative interviews provide valuable insights into the factors influencing medication adherence among Pakistani patients with cardiovascular conditions. While consistent adherence reflects patient acceptance and routine-based strategies, inconsistent adherence underscores financial constraints and medication-related challenges. Interventions tailored to address these barriers, including technology-based solutions and family support, could enhance medication adherence and improve cardiovascular health outcomes in the CVD population. Key Words: , , , .